Risk factors for complete uterine rupture in patients with trial of labor after cesarean delivery - Hortense Didier‐Mathon; Gilles Kayem; Thibault Thubert; Loîc Sentilhes; Charles Garabedian; Thomas Schmitz; Diane Korb; Edouard Lecarpentier; François Goffinet; Cyril Raiffort; Marie‐Victoire Senat; Elie Azria; et al. (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Vaginal birth after cesarean delivery (VBAC) attempt is promoted to reduce cesarean‐related morbidity, but it carries a risk of uterine rupture, posing significant maternal and neonatal risks. This study evaluated uterine rupture incidence and risk factors in a high VBAC attempt population. Material and Methods This was a 16‐year retrospective multicenter case–control cohort study (2002–2018). Eleven French university hospitals participated. Women were included if they had a complete uterine rupture during a VBAC attempt. Two controls, defined as a VBAC attempt without uterine rupture, were randomly included for each case. We analyzed the risk factors of uterine rupture among the overall population and then among women who had labor induction and those who had spontaneous labor. Logistic regression was used to compute crude odds ratios (ORs) and 95% confidence intervals (CIs) for uterine rupture. Multivariable logistic regression was used to calculate adjusted ORs (aORs) and 95% CIs. Results Among 48 124 patients with a single prior cesarean section, 31668 (65.8%, 95% CI 65.3–66.2) had a VBAC attempt and 23 086 (72.9% 95% CI 72.4–73.4) had a successful vaginal delivery. The complete uterine rupture frequency was 0.63%. There were 199 cases of complete uterine rupture (0.63%, 95%CI 0.54–0.71) and 396 controls. Among the overall population, the odds of uterine rupture was inversely associated with prior vaginal delivery (adjusted odds ratio [aOR] 0.3, CI 95% 0.2–0.5) and positively with induction of labor (aOR 2.2, 95% CI 1.4–3.4). For women with spontaneous labor, the odds of uterine rupture was positively associated with a Bishop score<6 (aOR 1.8, 95%CI 1.0–3.0), arrest of cervical dilatation of at least 1 hr. (aOR, 1.8 95%CI 1.1–2.9) and oxytocin augmentation (aOR 2.2 95% CI 1.3–3.7). For women undergoing labor induction, no factors were significantly associated with uterine rupture. Conclusions Uterine rupture frequency was low among women with high rates of VBAC attempt and successful vaginal delivery and was reduced with previous vaginal birth and increased with induction of labor, regardless of the method used. It was associated with any dystocia during spontaneous labor and suspected macrosomia in induced women, which should be managed with caution.